PENGARUH PERKEMBANGAN UMKM TERHADAP PERTUMBUHAN EKONOMI DI KAB. JENEPONTO - Aprizal Aprizal; Nurdiansyah Nurdiansyah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2023)
PDRB is an important measure that aims to determine the economic growth of a region within a country. Positive economic growth can be seen from the increasing GRDP rate. However, a field review conducted found a finding where the decline in the quality of MSMEs in Jeneponto Regency did not show a close relationship with regional economic growth in Jeneponto Regency which should have been based on previous research there was a strong link. Therefore, research was conducted with the aim of knowing the effect of MSME growth on economic growth in Jeneponto Regency for the 2018-2021 period. This study collected data using documentation techniques for a number of sub-district samples in Jeneponto Regency using a purposive sampling method. The number of samples obtained was 8 units, namely Bangkala, West Bangkala, Tamalatea, Binamu, Turatea, Kelara, Bontoramba, and Kec. Rumbia which was then analyzed using multiple linear regression.